Optimization of Selected Logistics Processes in a Courier Company - Jacek WOZNIAK (Communications of International Proceedings, 2021)
The article focuses on the discussion of selected logistics processes functioning in a courier service company. Processes were identified, discussed and evaluated in three company sectors, where specific solutions were implemented to optimize them. The objective of the paper is to identify the selected logistics processes together with the possibility of their optimization. On the basis of the collected data, an analysis of the implemented solutions was carried out and the benefits achieved by the company were indicated. The applied research methods, such as: literature analysis, comparative methods, outsider's observation, information analysis, deduction and inference allowed to achieve the intended objective. The literature review provided a basis for the analysis and presentation of conclusions concerning the discussed logistics processes. As a result of the research, the benefits that the company in question has achieved by optimizing three key logistics processes for its business were identified. The presented conclusions showed that sometimes difficult decisions from the company’s management, especially in the area of economic security, supported by effective planning, can bring the expected benefits.
Keywords: Courier industry; logistics processes; services; parcels; transport; sorting.